PERSEPSI MASYARAKAT TERHADAP KEBERADAAN BENDA CAGAR BUDAYA ISTANA KESULTANAN KADRIAH PONTIANAK TIMUR - Vioni Dwi Monika; Agus Sastrawan Noor; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research to determine the perception of the people who visit Kadriah Palace in East Pontianak as the objects of cultural heritage. This study used descriptive qualitative method. The data sources of this study was the manager of the Kadriah Sultanate Palace and community representatives who had visited. Data collection techniques used observation, interviews, and documentation. Results: (1) public perception about Kadriah Sultanate Palace positively, visitors argue that the palace still needs to be improved so that it remains a historical attraction that visitors can enjoy at any time. (2) preservation by the manager is already good in collaboration with the government, but it must be improved so that the Kadriah Sultanate Palace becomes a better historical attraction and well maintainece so that visitors feel comfortable when visit. (3) people's perception when visiting is to respond positively, their suggestions and hopes that the preservation of the Kadriah Sultanate Palace can be improved and when they visit, they get historical information well, but it is worth noting some deficiencies such as the addition of information boards, signs and additional guidelines so that all visitors become clearer in getting historical information.Keywords: Public perception,Cultural Heritage, Kadriah Sultanate Palace